Nota de los coordinadores de este monográfico - Costa Delgado, Jorge; López-Rabatel, Liliane; Moreno Pestaña, José Luis; Sintomer, Yves (Daimon Revista Internacional de Filosofia, 2017)
Nota de los coordinadores Jorge Costa Delgado, Universidad de Cádiz Liliane López-Rabatel, Institut de Recherche sur l’Architecture Antique José Luis Moreno Pestaña, Universidad de Cádiz Yves Sintomer, Université de Paris 8, Institut Universitaire de France